Intensive Glycemic Control for Diabetic Foot Ulcer Healing: A Multicentric, Randomized, Parallel Arm, Single-Blind, Controlled Study Protocol (INGLOBE Study). (December 2022) - Rastogi, Ashu; Mukhopadhyay, Satinath; Sahoo, Jay Prakash; Mennon, Arun; Ghosh, Amritava; Jha, Sujjet; Bal, Arun
Hyperglycemia impairs healing of diabetic foot ulcer (DFU). But there is no evidence regarding benefit of intensive glucose control for healing of DFU. We plan to conduct a randomized, parallel arm, controlled study to assess the role of intensive glycemic management in comparison to conventional glucose control for healing of DFU. Participants with neuropathic DFU (infected or uninfected) having hemoglobin A1c (HbA1c) >8% and without evidence of osteomyelitis from 7 tertiary care hospitals will be enrolled. They will undergo a 2-week run-in phase for optimization of comorbidities, ulcer debridement, and counseling regarding self-monitoring of blood glucose (SMBG). Subsequently, they will be randomized to "intensive glycemic control" arm defined by glycemic targets of fasting blood glucose (FBG) <130 mg/dL, postprandial BG <180 mg/dL, and HbA1c <8%, with basal-bolus insulin regimen and frequent titration of insulin to achieve glycemic targets. The "conventional" arm will continue on prior treatment (oral antidiabetic drugs) with no titration unless meeting rescue criteria. Ulcer area will be calculated by automated wound assessment device (WoundlyClinial app) weekly for first 4 weeks, and less frequently until the 24th week. Standard treatment for DFU, off-loading, and counseling for foot care will be provided in both arms. The primary outcome measure will be number of wounds closed at 12th and 24th weeks. A multivariate regression analysis will be performed to identify the predictors of wound healing with baseline HbA1c, diabetes duration, wound size, wound duration, and background therapies as independent variable. This study will provide the much needed guidance to set optimum glucose targets in people with DFU.